Attitudes towards Trilingual Education in Kazakhstan: A Case Study - Aubakirova, Rauza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The research focused on teacher and student attitudes towards trilingual education and its implementation in Kazakhstan. In addition, the purpose of the study was to investigate attitudes towards multilingual situation in Kazakhstan. The present study was conducted in Nazarbayev Intellectual School that practices trilingual education by teaching subjects within three languages: Kazakh, Russian, and English. It also attempted to investigate if there is correlation between teachers’ and students’ attitudes. Finally, the study aimed to find out whether gender affects the students’ attitudes. In the study, qualitative and quantitative methods were implemented. The participants involved 110 students from 9th, 10th, and 11th grades and 10 teachers of science subjects. All of the participants were non-native English speakers. The study employed triangulation: questionnaire, teacher interviews, and classroom observations. The results revealed that participants have positive or at least, neutral attitudes towards trilingual education and multilingual situation in Kazakhstan. Generally, students demonstrated more positive attitudes than their teachers. However, no statistically significant differences were found between teachers’ and students’ attitudes. Moreover, gender did not have a considerable effect on attitudes towards trilingual education as well as multilingual education.

ÖZ: Bu araştırma öğretmen ve öğrencilerin üç dilli eğitime karşı tutumunu ve üç dilli eğitimin Kazakistan’da uygulanmasına odaklanmıştır. Ek olarak, bu çalışmanın amacı Kazakistan’daki çok dillilik durumuna olan tutumu incelemektir. Bu çalışma üç dilde (Kazakça, Rusça ve İngilizce) eğitim veren bir okul olan Nazarbayev Intellectual School’da yapılmıştır. Ayrıca, bu çalışma öğretmenler ve öğrencilerin tutumların farklılıkları incelemeyi amaçlamıştır. Son olarak, bu çalışma öğrencilerin cinsiyet farkının üç dilliliğe olan tutumları üzerinde bir etkisi olup olmadığını incelemeyi hedeflemiştir. Bu çalışmada nitel ve nicel araştırma yöntemleri uygulanmıştır. Katılımcılar 9., 10. ve 11. sınıflardaki öğrencilerden oluşan 110 kişi ve 10 fen öğretmeninden oluşmaktadır. Bütün katılımcılar için İngilizce ana dil değildir. Çalışmada anket, öğretmen mülakatları ve sınıf gözlemleri yoluyla üçgenleme metodu kullanılmıştır. Bu çalışmanın sonuçları, katılımcıların üç dilliğe ve Kazakistan’daki çok dillilik durumuna karşı pozitif veya en azından, tarafsız tutumu olduğunu ortaya koymuştur. Genel olarak, sonuçlar öğrencilerin tutumlarının öğretmenlere göre daha pozitif olduğunu göstermiştir. Ancak, öğrenci ve öğretmen tutumları arasında istatistiksel olarak önemli bir farklılık bulunmamıştır. Ayrıca, cinsiyet farkının üç dilli eğitimine karşı tutumlar üzerinde de önemli bir etkisi olmadığı görülmüştür.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2017. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: English Language Teaching (ELT); Multicultural education--Multilingualism--Trilingual Education--Kazakhstan; Student attitude; teacher attitude; trilingual education; trilingualism; multilingualism; English medium of instruction